2020
DOI: 10.3389/fpls.2020.00735
|View full text |Cite
|
Sign up to set email alerts
|

The Leaf Economics Spectrum Constrains Phenotypic Plasticity Across a Light Gradient

Abstract: The leaf economics spectrum (LES) characterizes multivariate correlations that confine the global diversity of leaf functional traits onto a single axis of variation. Although LES is well established for traits of sun leaves, it is unclear how well LES characterizes the diversity of traits for shade leaves. Here, we evaluate LES using the sun and shade leaves of 75 woody species sampled at the extremes of a within-canopy light gradient in a subtropical forest. Shading significantly decreased the mean values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 79 publications
0
18
0
2
Order By: Relevance
“…As indicators of plant strategies (Violle et al, 2007;Westoby et al, 2002;Zhao, Ali, et al, 2016), functional traits affect (or at the very least reveal) life history and plant distribution characteristics (Díaz et al, 2004;Engelbrecht et al, 2007) involving trade-offs affecting plant growth and survival. For example, the leaf economics spectrum (LES) combines a series of interrelated leaf functional traits to quantitatively obtain pervasive plant resource trade-offs (Chen et al, 2021;Pan et al, 2020;Wright et al, 2004) that can predict the dynamics of community composition and the feedback of ecosystem functions (Chen et al, 2020;Reich et al, 1998;Wright et al, 2005). The LES has been extended to include the characteristics of wood (Chave et al, 2009) and later those of plant organs other than leaves (Kong et al, 2015;Roumet et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As indicators of plant strategies (Violle et al, 2007;Westoby et al, 2002;Zhao, Ali, et al, 2016), functional traits affect (or at the very least reveal) life history and plant distribution characteristics (Díaz et al, 2004;Engelbrecht et al, 2007) involving trade-offs affecting plant growth and survival. For example, the leaf economics spectrum (LES) combines a series of interrelated leaf functional traits to quantitatively obtain pervasive plant resource trade-offs (Chen et al, 2021;Pan et al, 2020;Wright et al, 2004) that can predict the dynamics of community composition and the feedback of ecosystem functions (Chen et al, 2020;Reich et al, 1998;Wright et al, 2005). The LES has been extended to include the characteristics of wood (Chave et al, 2009) and later those of plant organs other than leaves (Kong et al, 2015;Roumet et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we empirically showed that our spectra approach was accurate even when applied to new species or sites. We also think that our PLSR models could be applied more generally in the tropics, as there is a strong coordination among the traits of leaves and their function; known as the leaf economic spectrum [ 68 , 69 ]. This strong coordination could explain why a PLSR model trained on a sufficient number of species and conditions allowed that PLSR model to be sufficiently general for other species of the same biome [ 29 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, G max increased close to 1:1 with K and RR, whereas q Lcp and A max had less than proportional allometric relationships. Interestingly, scaling relationships between LES traits also have been shown to be similar in leaves at different canopy positions (Keenan and Niinemets, 2016;Chen et al, 2020), despite observed variations in allometric relationships between leaf functional traits in different conditions such as nutrient and water availabilities (Wright et al, 2001). The consistent slopes suggest that coordinated shifts among parameters are due to fundamental biological trade-offs.…”
Section: Discussionmentioning
confidence: 99%